Cooperative learning in peer teaching: A case study in an EFL context - Sunggingwati, Dyah (Universitas Pendidikan Indonesia, 2018)
It is significant to prepare pre-service teachers do to teaching practicum as they will teach English at secondary schools. One of the preparations is peer teaching during teacher education program. This study is intended to explore students’ experiences during the peer teaching in a cooperative learning style. One class of 26 students of English Education Department of a state university in East Borneo, Indonesia, participated in this study. They were randomly assigned in the group of four and eight, and each group member should practice peer teaching in their own group. Using a case study design, the findings have shown the potency of cooperative learning. The students had positive experiences the cooperative style of four-group, eight-group, and the whole class. The four- and eight- group formats in the peer teaching provide students more opportunities to have better teaching preparation, mastery of the teaching materials, more interaction with peers, to develop confidence, and to learn from others. They encountered some difficulties such as attracting peers’ attention, time for peer teaching, less serious peers, and more preparation. The findings suggest that it would be more valuable for students to be in more group formats with more time that would give students more confident when they teach for the whole class. Implication and suggestion are further discussed.